Expression of FMRpolyG in peripheral blood mononuclear cells of women with fragile X mental retardation 1 gene premutation - Nguyen, Xuan Phuoc; Vilkaite, Adriana; Messmer, Birgitta; Dietrich, Jens Erik; Hinderhofer, Katrin; Schäkel, Knut; Strowitzki, Thomas; Rehnitz, Julia (Genes, 2022)
Fragile X-associated primary ovarian insufficiency (FXPOI) is characterized by oligo/amenorrhea and hypergonadotropic hypogonadism and is caused by the expansion of the CGG repeat in the 5′UTR of Fragile X Mental Retardation 1 (FMR1). Approximately 20% of women carrying an FMR1 premutation (PM) allele (55-200 CGG repeat) develop FXPOI. Repeat Associated Non-AUG (RAN)-translation dependent on the variable CGG-repeat length is thought to cause FXPOI, due to the production of a polyglycine-containing FMR1 protein, FMRpolyG. Peripheral blood monocyte cells (PBMCs) and granulosa cells (GCs) were collected to detect FMRpolyG and its cell type-specific expression in FMR1 PM carriers by immunofluorescence staining (IF), Western blotting (WB), and flow cytometric analysis (FACS). For the first time, FMRpolyG aggregates were detected as ubiquitin-positive inclusions in PBMCs from PM carriers, whereas only a weak signal without inclusions was detected in the controls. The expression pattern of FMRpolyG in GCs was comparable to that in the lymphocytes. We detected FMRpolyG as a 15- to 25-kDa protein in the PBMCs from two FMR1 PM carriers, with 124 and 81 CGG repeats. Flow cytometric analysis revealed that FMRpolyG was significantly higher in the T cells from PM carriers than in those from non-PM carriers. The detection of FMRpolyG aggregates in the peripheral blood and granulosa cells of PM carriers suggests that it may have a toxic potential and an immunological role in ovarian damage in the development of FXPOI.